2019
DOI: 10.3390/molecules24030534
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Proteomimetic Quinazolinone Alkaloids and Evaluation of Their Neuroprotective and Antitumor Effects

Abstract: New quinazolinone derivatives of the marine-derived alkaloids fiscalin B (3) and fumiquinazoline G (1), with neuroprotective and antitumor effects, were synthesized. Eleven quinazolinone-containing indole alkaloids were synthesized, proceeding the anti analogs via a one-pot method, and the syn analogs by the Mazurkiewicz-Ganesan approach. The neuroprotection capacity of these compounds on the rotenone-damage human neuroblastoma cell SH-SY5y was evaluated using the MTT assay. Compounds 1, 3, 5, and 7 showed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…Many 3,4-dihydroquinazolin-2(1 H )-one derivatives have been previously synthesized (Huang et al, 2008; Khan et al, 2014, 2015, 2016; Kshirsagar, 2015; Camacho et al, 2016; Maiden and Harrity, 2016; Awad et al, 2018; Zhang et al, 2018; Elkholy et al, 2019; Gatadi et al, 2019; Long et al, 2019; Wang et al, 2019). For example, Wang et al (2009) reported the synthesis of 4-alkyl-2(1H)-quinazolinones via the cyclization of 1-(2-alkynyl-phenyl)ureas catalyzed by TfOH and Saunthwal et al (2015) described a green and catalyst-free straightforward tandem synthesis of functionalized tetrahydroquinazolines from 2-aminophenylacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…Many 3,4-dihydroquinazolin-2(1 H )-one derivatives have been previously synthesized (Huang et al, 2008; Khan et al, 2014, 2015, 2016; Kshirsagar, 2015; Camacho et al, 2016; Maiden and Harrity, 2016; Awad et al, 2018; Zhang et al, 2018; Elkholy et al, 2019; Gatadi et al, 2019; Long et al, 2019; Wang et al, 2019). For example, Wang et al (2009) reported the synthesis of 4-alkyl-2(1H)-quinazolinones via the cyclization of 1-(2-alkynyl-phenyl)ureas catalyzed by TfOH and Saunthwal et al (2015) described a green and catalyst-free straightforward tandem synthesis of functionalized tetrahydroquinazolines from 2-aminophenylacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…These media were supplemented with 5% FBS for the cell growth inhibition assay (SRB) or with 10% FBS for the remaining experiments. The non-tumorigenic cell line MCF-12A was cultured in RPMI 1640 medium supplemented with hEGF (human epidermal growth factor; 20 ng/μL), hydrocortisone (500 ng/μL), 5% FBS and 1% Penicillin-Streptomycin (Gibco), as previously described [ 30 ]. All the cell lines were maintained as adherent cell cultures and kept at 37 °C in a humidified incubator containing 5% of CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was done as mentioned before [41]. MTT solution (4 mg/mL in PBS) was added (20 μL/well) into each well and incubated with cells for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%